1977
DOI: 10.4141/cjas77-033
|View full text |Cite
|
Sign up to set email alerts
|

The Dry Matter Intake and Digestibility of Winter Wheat Harvested as Whole Crop Silage

Abstract: Ftsut,n, L. J. rNo LEssano, J. R. lgjj. Thc dry mattcr inrake an Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We speculate that high concentrate content and wheat silage proportion resulted in great CP and low ADF content, and further led to high ADG. However, in the study of Fisher and Lessard (1977) , cows fed wheat silage instead of corn silage lost live weight compared to the initial, whilst milk yield and composition were not altered. Unlike lambs, cows partitioned dietary energy toward lactation, thus sacrificing the energy for maintenance and growth.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We speculate that high concentrate content and wheat silage proportion resulted in great CP and low ADF content, and further led to high ADG. However, in the study of Fisher and Lessard (1977) , cows fed wheat silage instead of corn silage lost live weight compared to the initial, whilst milk yield and composition were not altered. Unlike lambs, cows partitioned dietary energy toward lactation, thus sacrificing the energy for maintenance and growth.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies noted that the nutritive value, silage quality, and feeding effect would vary depending on the different maturity stages of wheat silage. For instance, wheat crops harvested at the milk stage owned high fermentation quality, while those harvested at the dough stage had high forage value ( Fisher and Lessard, 1977 ; Randby et al., 2019 ; Xie et al., 2012 ). It was reported that wheat silage at the dough stage had a comparatively higher DM content than corn silage ( Turan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%